9-3x=-2x+8

Simple and best practice solution for 9-3x=-2x+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9-3x=-2x+8 equation:


Simplifying
9 + -3x = -2x + 8

Reorder the terms:
9 + -3x = 8 + -2x

Solving
9 + -3x = 8 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
9 + -3x + 2x = 8 + -2x + 2x

Combine like terms: -3x + 2x = -1x
9 + -1x = 8 + -2x + 2x

Combine like terms: -2x + 2x = 0
9 + -1x = 8 + 0
9 + -1x = 8

Add '-9' to each side of the equation.
9 + -9 + -1x = 8 + -9

Combine like terms: 9 + -9 = 0
0 + -1x = 8 + -9
-1x = 8 + -9

Combine like terms: 8 + -9 = -1
-1x = -1

Divide each side by '-1'.
x = 1

Simplifying
x = 1

See similar equations:

| -8x^2+128=0 | | 8m+6=3(m+2) | | 7x+14=2x+149 | | 5+6x=-6x+113 | | 0=-10v^2+13v+3 | | 3x-7=-1+6x | | 2(8+4k)=3k-4 | | -2x+1=-5x+31 | | 4(8-6x)=5x-26 | | 5x^2+75x+270=0 | | x+8=-16+4x | | 32+6x=8(x+3) | | 2(5x-25)=10(x-5) | | 6+3x=-3x-6 | | -7x^2-64+112=0 | | -9+5x=3x+9 | | 2(7v+7)=28+7v | | 7-7x=2x+7 | | 11x^2-37x=0 | | 2(1-2n)=2n+8 | | -9+2x=4x-17 | | 18x^2+3x-10=0 | | -4x^2-4x+168=0 | | 3-x=8(1-6x)-5 | | 7m^2-35m=0 | | 6x^2+42x+60=0 | | 9m^2-54m=0 | | 6x+9=199-5x | | 8+4r=8(-7r+1) | | 6(1+2k)=-k+19 | | X-2(x-3)=-6-5x | | 2-m(5+mx)=3m^2(1-mx) |

Equations solver categories